Peculiarities of changes of autonomic nervous system functional state in patients with measles - O. Yu. Pavlenova; L. A. Ushenina; E. V. Ryabokon (Zaporožskij Medicinskij Žurnal)
In patients with measles we revealed the decrease of parameters of general power of vegetative regulation and power of spectra of humoral influences with the development of vegetative imbalance towards the parasympathicotonia. In the dynamics of the disease in convalescence period we noted the increase of the total power of heart rate variability and sympathetic activity, although these indices are reduced as compared with healthy people ones.